Study of The Relevance of The Early Retirement Plan for Moroccan Civil Servants via Discrete Simulation - Khadija Ouazzani-Touhami; Mohammed El Arass; Nissrine Souissi (Statistics, Optimization & Information Computing, 2022)
The supervision of a complex system involves the study and analysis of its operation as well as a continuous search for its improvement and optimization. Simulation in general, and discrete simulation in particular, is an appropriate tool to support different management policies and strategies. In order to carry out a simulation project, special importance must be given to the simulation process, which has led us in this paper to ask the question: is there a standard life cycle of a simulation project? or a repository of the steps to follow? In this paper, we have used the most frequently cited simulation steps in the literature to develop a simulation project life cycle called SPLC (Simulation Project Life Cycle) grouping together the main steps. Then, we were interested in the analysis of the level of use of each of the steps retained by the simulation processes described in the simulation studies considered in the literature review. Secondly, we tried to put the elaborated SPLC cycle into action through a simulation case study, this is the voluntary departure operation launched in Morocco in 2005. Thus, we carried out a simulation allowing to analyze the success rate of this operation, and also its impact on the state of the Moroccan pension fund, and this for the period going from 2005 to 2025. The study was carried out on a set of generated data randomly according to statistical distributions.